2020
DOI: 10.3390/toxins12080498
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxin M1 in Raw Milk from Different Provinces of Ecuador

Abstract: Aflatoxin M1 (AFM1) is a mycotoxin from Aspergillus flavus and A. parasiticus, classified as carcinogenic and hepatotoxic. The objective of the present investigation was to determine its presence in raw milk from north-central Ecuador, constituted by the provinces of Pichincha, Manabí, and Santo Domingo de los Tsáchilas. These areas represent approximately 30% of Ecuadorian milk production. By the end of the investigation, a total of 209 raw milk samples were collected, obtained both during the dry (June and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…However, higher than the other studies conducted in Egypt (Ismaiel et al., 2020 ) and two studies from Turkey (Yilmaz et al., 2019 ). The mean value of AFM1 of this study was comparable with the study conducted in Addis Ababa but higher than the result reported from Peru (Puga et al., 2020 ) and Argentina (Costamagna et al., 2019 ) and lower than the study found in Egypt (Temamogullari et al., 2014 ). This variation in milk AFM1 level could be due to milk originating from different agroecological conditions, applying different feeding practices, different climate conditions, different cattle management systems, feed storage conditions, and different levels of awareness on milk AFM1.…”
Section: Discussionsupporting
confidence: 77%
“…However, higher than the other studies conducted in Egypt (Ismaiel et al., 2020 ) and two studies from Turkey (Yilmaz et al., 2019 ). The mean value of AFM1 of this study was comparable with the study conducted in Addis Ababa but higher than the result reported from Peru (Puga et al., 2020 ) and Argentina (Costamagna et al., 2019 ) and lower than the study found in Egypt (Temamogullari et al., 2014 ). This variation in milk AFM1 level could be due to milk originating from different agroecological conditions, applying different feeding practices, different climate conditions, different cattle management systems, feed storage conditions, and different levels of awareness on milk AFM1.…”
Section: Discussionsupporting
confidence: 77%
“…Since 1970, the popularity of the use of immunoenzymatic methods has increased in the analysis of mycotoxins (Singh & Mehta, 2020 ). In recent years, ELISA test kits are used to determine concentration of mycotoxins such as patulin (PAT), aflatoxins (AFs, AFB 1 ), ochratoxins (OTA), zearalanone (ZEN), trichothecenes, fumonisins (FBs), citrinin (CIT) in food samples, and agricultural commodities (Azam et al., 2021 ; Omar et al., 2020 ; Puga‐Torres et al., 2020 ; Sudakin & Fallah, 2008 ; Tang et al., 2019 ). The ELISA technique has also been used in herbal raw materials such as black pepper, coriander, ginger, garlic, and plants belonging to the Fabaceae family also (Dungkokkruad et al., 2017 ; Orina et al., 2020 ; Thirumala‐Devi et al., 2001 ; Tonti et al., 2017 ; L. Zhang et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, ELISA test kits are used to determine concentration of mycotoxins such as patulin (PAT), aflatoxins (AFs, AFB 1 ), ochratoxins (OTA), zearalanone (ZEN), trichothecenes, fumonisins (FBs), citrinin (CIT) in food samples, and agricultural commodities (Azam et al, 2021;Omar et al, 2020;Puga-Torres et al, 2020;Sudakin & Fallah, 2008;Tang et al, 2019…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…In milk, ZEA is frequently found together with ochratoxin A or aflatoxin M1 (AFM1) [49]. This is important because, in a parallel study, AFM1 was found in the same raw milk in 100% of the samples, with a mean of 0.0774 µg/kg [50].…”
Section: Discussionmentioning
confidence: 99%